Die joodse volk en die kerk: nog 'n beskouing van die Probleem - Keane, Marie Henry (Koers, 1989)
The Jewish nation and church: Another view of the problem. This article takes a look at the "Jewish problem" using Roman 9-11 as the point of departure . The apostle Paul is convinced that God has not rejected Israel. The Jews s till have a decisive role to p la y in the divine action in history . The problem o f the Jewish -Christian relationship is as old as Christianity itself. On this article the writer does not attempt to offer solutions b u t reminds the church that the people o f God will be incomplete until Jews and Christian s alike are united .